Pathological potential of astroglia - Chvátal, Alexandr; Anděrová, Miroslava; Neprašová, Helena; Prajerová, Iva; Benešová, Jana; Butenko, Olena; Verkhratsky, A (Physiological research, 2008)
The pathological potential of glial cells was recognized already by Rudolf Virchow, Santiago Ramon y Cajal and Pio Del Rio-Ortega. Many functions and roles performed by astroglia in the healthy brain determine their involvement in brain diseases; as indeed any kind of brain insult does affect astrocytes, and their performance in pathological conditions, to a very large extent, determines the survival of the brain parenchyma, the degree of damage and neurological defect. Astrocytes being in general responsible for overall brain homeostasis are involved in virtually every form of brain pathology. Here we provide an overview of recent developments in identifying the role and mechanisms of the pathological potential of astroglia.
Keywords: Gliosis; Potassium; Extracellular Space; neurony; Gap Junctions; mezerový spoj; Brain Diseases; Rats; glióza; Neurotransmitter Agents; nemoci mozku; Neurons; Synapses; Brain; astrocyty; lidé; draslík; reaktivní formy kyslíku; mozek; neurotransmiterové látky; Animals; Astrocytes; krysa rodu Rattus; Humans; synapse; extracelulární prostor; zvířata; Reactive Oxygen Species